PENGARUH BUDAYA ORGANISASI, KONDISI KERJA, DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI PADA PT. PLN (PERSERO) UNIT INDUK DISTRIBUSI BALI - I Putu Bagus Ade Satyawan; Ni Nyoman Suryani; Ni Putu Yeni Astiti (VALUES, 2023)
Job satisfaction is a condition in which employees reflect pleasure at work. Job satisfaction of each employee is different. The more aspects of work that are in accordance with the wishes of the individual, the higher the level of satisfaction felt and if employee job satisfaction is considered, the employee will work to the best of his ability to obtain what is expected at work. This study aims to determine the partial and simultaneous effect of organizational culture, working conditions, and workload on employee job satisfaction at PT. PLN (Persero) Bali Distribution Main Unit. The research population was employees of PT. PLN (Persero) Bali Distribution Main Unit, the sample was determined using the slovin formula and the results were 85 respondents. The analytical tool used to test the hypothesis is multiple linear regression. Based on the results of the study, it shows that organizational culture has a positive and significant effect on job satisfaction, working conditions have a positive and significant effect on job satisfaction, and workload has a positive and significant effect on job satisfaction. The magnitude of the influence of the independent variables on the dependent variable in this study is 40.5%. Further research can develop this research by using other variables that can affect employee job satisfaction.